The Epistemological Foundations of Freud’s Energetics Model - Tran The, Jessica; Magistretti, Pierre; Ansermet, François (Frontiers in Psychology, 2018)
This article aims to clarify the epistemological foundations of the Freudian energetics model, starting with a historical review of the 19th century scientific context in which Freud’s research lay down its roots. Beyond the physiological and anatomical references of Project for a Scientific Psychology (Freud, 1895a), the physiology Freud makes reference to is in reality primarily anchored in an epistemological model derived from the science of physics. Whilst across the Rhine, the autonomy of physiology in relation to physics was far from being accomplished, as a counterpoint, in France, the revolution in physiology driven by Claude Bernard established itself autonomously in relation to physics,. In contrast, Freud’s scientific landscape is entirely dominated by the science of physics elevated to the rank of an ideal science. The influence of Helmholtz, who is both a medical man and a physicist, has a determining influence on Freud’s training. The discoveries in physics at this time, in particular the formulation of the principle of ‘conservation of force’ – first principle of thermodynamics – will constitute the points of reference on which Freud will elaborate his energetics model, then subsequently, the idea of economy in his metapsychology. In this way we can retrace both the historic and epistemological path that will lead Freud from a concept based on physics, and more specifically thermodynamic energy, to an idea of nervous energy that constitutes the basis of the concept of “quantity” as it is sated as ‘first fundamental idea’ in Project for a Scientific Psychology (Freud, 1895a). Something that will subsequently evolve, and lead Freud to the introduction of the concept of ‘psychic energy’, this time in a purely metapsychological sense.